Buprenorphine tablet versus liquid: a clinical trial comparing plasma levels, efficacy, and symptoms. - Chawarski, Marek C; Moody, David E; Pakes, Juliana; O'Connor, Patrick G; Schottenfeld, Richard S (Journal of substance abuse treatment, 2005)
We evaluated peak plasma concentrations, trough concentrations, and the 24-hour area under the concentration curve (AUC(0-24 h)) during maintenance with sublingual (SL) liquid or tablet formulations in 57 opiate-dependent volunteers. Study participants were assigned randomly to one of three SL daily buprenorphine dose pairs and maintained for 2 weeks with the liquid formulation followed by 2 weeks with the corresponding tablet dose. Plasma samples were obtained after at least 10 days of maintenance with the liquid formulation and after at least 10 days of that with the tablet formulation. The bioequivalence of the tablet compared with the liquid doses ranged from 57% to 75% based on peak concentrations, from 102% to 108% based on trough concentrations, and from 66% to 86% based on 24-hour AUC, but there was a large intersubject and intrasubject variability in plasma concentrations, with greater variability following tablets than liquid. Measures of withdrawal symptoms or illicit opioid use were not associated with buprenorphine dose, formulation, or plasma buprenorphine levels.
Keywords: Administration, Sublingual; Adult; Buprenorphine; Female; Humans; Male; Metabolic Clearance Rate; Middle Aged; Narcotic Antagonists; Opioid-Related Disorders; Pharmaceutical Solutions; Substance Withdrawal Syndrome; Tablets; Treatment Outcome